Beyond Conventional CSR Theory: The Development of the PUSAKA KELUANG CSR Program as a Systemic Social Innovation - Iwan Ridwan Faizal; Dedi Zikrian S; Rara Ayuni Rahmadani; Fatika Hastigerina Ananda; Dedo Kevin Prayoga (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2026)
This study aims to examine the evolution of conventional Corporate Social Responsibility (CSR) toward systemic Corporate Social Innovation (CSI) through the implementation of the PUSAKA KELUANG Program by PT Pertamina EP Ramba Field and the community of Keluang Village. A qualitative method was employed with a desk research approach, examining social innovation documents and utilizing primary data obtained from program coordinators and beneficiaries. The findings indicate that the integration of four main pillars, including health, environment, economy, and food security, has successfully addressed the village’s structural problems. The program has proven successful because it places vulnerable groups, such as women and underprivileged communities, to be able to change vulnerability into resilience. It can be concluded that corporate social innovation cannot run independently but instead requires integrated multisectoral collaboration that can overcome sectoral egoism, as well as the application of bottom-up, creating shared value (CSV) principles to foster ecological resilience and sustainable communal self-reliance.